PENGARUH KEMAMPUAN, PELATIHAN, DAN PENGALAMAN KERJA TERHADAP EFEKTIVITAS KERJA KARYAWAN DI PT. SINAR JENIH SARANA - Habib Rangkuti; Ramadhan Ramadhan; Muhammad Isa Indrawan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This research was conducted in PT. Sinar Jernih Sarana Medan which aims to find out how the influence of Ability (X1), Training (X2), and Work Experience (X3) on Work Effectiveness (Y) of employees at PT. Sinar Jernih Sarana Medan. The population in this study are employees of PT. Sinar Jernih Sarana Medan, which has 154 employees, while the number of samples taken is 61 employees. The study was conducted from February to October 2021. This study used quantitative data that was processed with the SPSS version 24.0 application with multiple linear regression models. Sources of data used primary data taken directly from the respondents. The results showed that ability, training, and work experience had a positive and significant effect either partially or simultaneously on the work effectiveness of PT. Clear Rays of Medan Facilities.